Wide field scanning by optical fluorescence of oral squamous cell carcinoma (SCC): case report - Ismael Lucas PINTO; Jairo G. CARLOS; Ana Paula OLIVEIRA DE ARAÚJO; Clóvis Milton Duval WANNMACHER (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Optical fluorescence detection aims to identify precursor lesions, little noticeable to the human eye, and oral cancer. Squamous cell carcinoma or spinocellular carcinoma is a malignant neoplasm that affects the mouth more. In this article, two clinical cases are analyzed, treated with the use of two types of equipment, namely: the photoevidenciation by optical fluorescence of light-emitting violet wavelength of 405nm, power of 100mW, which is luminous radiation, not Ionizing and in the adjuvant treatment, we used low-power laser therapy, power 100mW, with two wavelengths of 808nm infrared, for pain relief, and the red 660nm, for oral mucositis. In Photodynamic therapy, the Photosensitizing Chimiolux® (methylene blue) was used to control Candida albicans. From these cases, we discuss how a more assertive diagnostic hypothesis can save a life and save time, resources, and efforts for the correct diagnosis of the pathology compared to a biopsy and histopathology negative for neoplasia. We conclude that optical fluorescence has excellent social relevance due to its potential to help the professional not specialized in the establishment of early diagnosis of oral cancer. Early diagnosis improves the rates of death caused by this carcinoma, which would extend the post-diagnosis survival and decrease the financial and emotional costs for the patient and family.